664.8 Qishloq xo’jaligi mahsulotlarini yetishtirish, saqlash qayta ishlash va oziq-ovqat texnologiyalari: Research in beverage technology intended to support the functions of the cardiovascular system - Nishonov, O'tkirali (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
This article is devoted to the study of beverage technology designed to maintain the functions of the human cardiovascular system. In the work, marigolds, a plant of the genus Tagetes (Asteraceae), rich in flavonoids with cardioprotective, antimicrobial, hypotensive, hepatoprotective effects, were considered as raw materials.